Ursachen und Wirkungen eines zwischenstaatlichen Finanzausgleichs - Stefan Homburg (Fiskalföderalismus in Europa, 1997)
The article concerns issues of fiscal federalism in the broadest sense. It analyzes both the political causes and the economic consequences of interregional and international grants. Examples from Germany and from the European Union are considered. – – Der Artikel behandelt den Finanzausgleich im weitesten Sinne. Er analysiert sowohl die politischen Ursachen als auch die ökonomischen Konsequenzen zwischenstaatlicher Transfers. Als Beispiele dienen Deutschland und die Europäische Union.
Keywords: H73; H77; 330; Fiscal federalism; intergovernmental grants; Fiskalföderalismus; Finanzausgleich